2012
DOI: 10.1177/003172171209400203
|View full text |Cite
|
Sign up to set email alerts
|

Learning 21st-Century Skills Requires 21st-Century Teaching

Abstract: New styles of instruction Globalization, economic necessity, and low civic engagement compound the urgency for students to develop the skills and knowledge they need for success. The interconnectedness of our global economy, ecosystem, and political networks require that students learn to communicate, collaborate, and problem solve with people worldwide. Employers demand fewer people with basic skill sets and more people with complex thinking and communication skills (Levy & Murnane, 2005). Low levels of civic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
286
0
58

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(350 citation statements)
references
References 9 publications
6
286
0
58
Order By: Relevance
“…Teaching and learning processes have become more interactive, engaging and fun through technology-based instruction. With the integration of technology in the classroom, educators continue to create learning materials that are innovative, task-oriented as well as learner-centered (Saavedra & Opfer, 2012;Kim, Choi, Han & So, 2012;Tindowen, Bassig & Cagurangan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Teaching and learning processes have become more interactive, engaging and fun through technology-based instruction. With the integration of technology in the classroom, educators continue to create learning materials that are innovative, task-oriented as well as learner-centered (Saavedra & Opfer, 2012;Kim, Choi, Han & So, 2012;Tindowen, Bassig & Cagurangan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This condition requires students to learn how to communicate, cooperate, and solve problems with people all over the world. Students need seven survival skills including: critical thinking and problem solving, leadership and cooperation, agility and adaptability, full of initiative and enterprener spirit, ability to communicate effectively both oral and written, easy access to information and information analysis, imagination and curiosity (Saavedra & Opfer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [5] found that using testing for secondary students" evaluation was not suited to 21st century teaching. How teachers relate to their students, motivate them and give them pathways to unlock their potential, is more important.…”
Section: Literature Reviewmentioning
confidence: 99%